Effect of vegetable-based oil blends on physicochemical properties of oils during deep-fat frying. - Serjouie, Alireza; Tan, Chin Ping; Mirhosseini, Hamed; Che Man, Yaakob (Academic Journals Inc., USA, 2010)
Frying performance of palm olein, sesame oil and canola oil and their blends was investigated by assessing the physicochemical changes (i.e., color, viscosity, Free Fatty Acid (FFA), Peroxide Value (PV), Anisidine Value (AV), TOTOX Value (TV), Polymer Content (PC) and specific extinction) of oils during deep-fat frying of potato chips. Six frying oils, namely refined, bleached and deodorized (RBD) palm olein (A), canola oil (C), RBD palm olein/sesame oil (AB, 1:1 w/w), RBD palm olein/canola oil (AC, 1:1 w/w), sesame oil/canola oil (BC, 1:1 w/w) and RBD palm olein/sesame oil/canola oil (ABC, 1:1:1 w/w/w) were considered as the independent variables. The physicochemical properties of the frying oils were significantly (p<0.05) influenced by the type and concentration of the component oil(s). Among all six frying oils, canola oil (C) generally exhibited the least chemical stability during the frying process and RBD palm olein (A) the highest.